Analisis Faktor Fundamental Gizi Yang Mempengaruhi Performa Atlet Handball - Arinda, Ditia Fitri; Rifalia, Grachefa Asyel; Raihana, Jasmine; Fajra, Ridzki Mulya (Jurnal Sporta Saintika, 2025)
Indonesia's sports achievements seem to experience inconsistent fluctuations. Therefore, various aspects related to the development of high-performance sports need to be considered. Currently, there are risks that can increase the possibility of body image problems in athletes, one of which is social pressure from coaches. Athletes who cannot maintain good body composition can become overweight to obesity. Athletes and coaches must have nutritional knowledge, especially regarding food management during training periods, competition periods, and recovery periods. The sample in this study was 64 handball athletes in Palembang City who were taken using the total sampling technique. The data analysis technique used the Chi-square test. The results of this study showed that most of the Palembang handball athletes in this study had a positive body image, muscle mass was in the high category, fat levels were in the normal category, and knowledge was in the sufficient category. The results of this study indicate that body image does not affect the performance of handball athletes in Palembang City (p = 0.917), knowledge does not affect the performance of handball athletes in Palembang City (p = 0.132), fat levels do not affect the performance of handball athletes in Palembang City (0.446), and muscle mass does not affect the performance of handball athletes in Palembang City (p = 0.286). The researcher recommends that coaches improve athlete performance by increasing the frequency of training and for further research to conduct further research by changing or adding variables and increasing the number of samples.